Production of Algae-Derived Biochar and Its Application in Pollutants Adsorption—A Mini Review - Luyang Li; Jinfeng Wang; Weiming Sun; Xinhong Peng; Xinhua Qi (Separations)
Developing algae cultivation for food, chemicals, and bio-energy generates a significant amount of algal waste/residue after utilization. Meanwhile, harmful algal blooms caused by abnormal proliferation of various algae produce a large amount of algal biomass, posing serious harm to human health, the environment and the economy. Converting algae body to biochar is a crucial method with which to take advantage of this resource. Biochar usually has a large specific surface area, developed pore structure, high cation exchange capacity and rich surface functional groups. With the advantage of stable physical/chemical properties and easy modification techniques, biochar posited as an ideal adsorption material. From the perspective of algal biomass utilization, this paper reviews the preparation and modification methods, structural characteristics, physicochemical properties and environmental implications of algal biochar. The adsorption effect and mechanisms of algal biochar on nutrients, heavy metals, and organic matter in water are introduced. In light of the current research status, the challenges faced in practical application of algae-derived biochar adsorption materials are pointed out, and a research direction for preparation and application is also developed, with a view to providing a reference for the further utilization of algae-derived biochar.